THE EFFECT OF DIETARY OILS AND HYDROLYZED COCONUT OIL ON MINERALS ABSORPTION IN RATS. - Margata, Linda; Silalahi, Jansen; Harahap, Urip; Satria, Denny (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to investigate the effect of coconut oil (virgin coconut oil; VCO), corn oil, palm oil, and hydrolyzed VCO (HVCO) on minerals (calcium and magnesium) absorption in rats. Methods: The oils used were corn oil, palm oil, VCO, and HVCO. VCO hydrolysis was done using lipase from Rhizomucor miehei (active on sn-1,3 position). The effect of oils and HVCO on minerals absorption was carried out on 25 male rats, weighing approximately 150–200 g. Rats were housed in air-conditioned room at 22–25°C, under 12-light/dark cycle, fed on basal diet and tap water ad libitum. After 1-week acclimatization, rats were given oils and HVCO for 21 days. The effect of oils on the minerals absorption were determined over the 4-day metabolic balance study. Mineral concentrations in diet, feces, urine, and serum were measured using atomic absorption spectrometry. Minerals absorption are expressed as apparent minerals absorption, apparent minerals absorption rate, and apparent minerals balance. Results: Calcium absorption in rats given with VCO, corn oil, palm oil, and HVCO is 47.09%, 45.46%, 44.48%, and 49.33%, respectively, whereas, magnesium absorption in rats given with VCO, corn oil, palm oil, and HVCO is 34.87%, 32.08%, 29.39%, and 37.11%, respectively. The results of this study show that minerals absorption in rats given with dietary oils is significantly lower than the control group (51.79% for calcium and 42.34% for magnesium). Mineral absorption in rats given with HVCO results in the highest rate of all rats given with the other oils tested. Conclusion: Corn oil and palm oil, which belong to the long chain triglycerides oil, lower calcium, and magnesium absorption more significantly than VCO as a medium chain triglyceride oil does. HVCO results in significantly higher calcium and magnesium absorption compared to non-HVCO.